2008
DOI: 10.1016/j.juro.2008.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Consumer Trial Performance of a Sensitive Immunodiagnostic Home Test That Qualitatively Detects Low Concentrations of Sperm Following Vasectomy

Abstract: Purpose Compliance with post-vasectomy semen analysis could be improved with the availability of a simple, rapid and accurate home test. SpermCheck Vasectomy®, a highly sensitive lateral flow immunochromatographic diagnostic device, was designed to detect extreme oligospermia or azoospermia in men after vasectomy. We report the results of clinical and consumer testing of SpermCheck. Materials and Methods A prospective, noncomparative observational study assessed the ability of SpermCheck Vasectomy to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Other studies included questionnaires on various aspects of performing the home tests and found that most participants indicated by their responses that they knew how to perform the tests [18, 19]. …”
Section: Resultsmentioning
confidence: 99%
“…Other studies included questionnaires on various aspects of performing the home tests and found that most participants indicated by their responses that they knew how to perform the tests [18, 19]. …”
Section: Resultsmentioning
confidence: 99%
“…Drawbacks to vasectomy include the fact that it is surgical and not easily reversed [11 ]. Although vasectomy requires semen analysis to insure efficacy, a home test that can provide reliable information about sperm counts was recently approved by the Food and Drug Administration [12 ]. Complications from the surgery include bleeding and hematoma, sperm granulomas, chronic pain, and epididymitis.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…SpermCheck Vasectomy ®). Such methods are already FDA approved and currently many couples confirm near azoospermia post-vasectomy before ceasing other contraceptive methods 58 . These techniques can be used to assess male infertility 59 and even more sensitive fluorescent methods are being developed for home use 60 .…”
Section: 4 Alternative Approachesmentioning
confidence: 99%